Le théâtre du Grand-Guignol et l’esthétique du féminicide - Rimpei Mano (Criminocorpus)
This article examines the aestheticization of feminicide in the Grand-Guignol theatre. At the beginning of the 20th century, this theatre made feminicide, a popular theme in the popular press, a major subject in its repertoire. The theatre's founder, Oscar Méténier, in Lui! depicts the violence of a male murderer against a prostitute. The theatre's favourite actress, Maxa, "the most murdered woman in the world", herself embodies the aesthetics of feminicide, of which Pierre Chaine's Le Jardin des Supplices offers one of the best results. But Eugène Héros and Léon Abric's La Veuve seems to defy this aesthetic by presenting a heroine sexually excited by the sight of death. This caricatured comedy, which introduces a reversal of sexual roles, is likely to reject the misogynistic ideology of the Grand-Guignol theatre.